It's a equation of the circle.
The standard form equation of a circle:
[tex](x-h)^2+(y-k)^2=r^2[/tex]
where (h; k) - the coordinates of the center of the circle
r - the radius
We have:
[tex]x^2+y^2-8x+6y+5=0[/tex]
Use: [tex](a\pm b)^2=a^2\pm 2ab+b^2[/tex]
[tex]x^2-8x+y^2+6y+5=0\\\\\underbrace{x^2-2\cdot x\cdot4+4^2}_{(a-b)^2=a^2-2ab+b^2}-4^2+\underbrace{y^2+2\cdot y\cdot3+3^2}_{(a+b)^2=a^2+2ab+b^2}-3^2+5=0\\\\(x-4)^2+(y+3)^2-16-9+5=0\\\\(x-4)^2+(y+3)^2-20=0\ \ \ |+20\\\\(x-4)^2+(y+3)^2=20\\\\(x-4)^2+(y+3)^2=(\sqrt{20})^2\\\\(x-4)^2+(y+3)^2=(2\sqrt5)^2[/tex]
The center of the circle (4; -3).
The length of radius 2√5.